2001
DOI: 10.14214/sf.576
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagated silver birches (Betula pendula) in the field – performance and clonal differences

Abstract: Micropropagated and seed-born silver birches (Betula pendula Roth) were compared for survival, height growth and occurrence of biotic damage (voles, hares, mooses, stem lesions and cankers) in fi eld trials in southern Finland. The material consisted of 11 clones and 10 different lots of seedlings growing in 10 fi eld trials, established in clearcut forest cultivation areas. The plants were 6-7 years old. The micropropagated and seed-born material types did not signifi cantly differ from each other as regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…The plantlets showed the 100% survival rate (data not shown). The successful establishment of plantlet in this study was due to their micropropagation origin that is contrary to the report for Betula pendula (45). Some plantlets grow faster and exhibited higher values for all the parameters evaluated than the donor plant (see Table 3).…”
Section: Discussioncontrasting
confidence: 85%
“…The plantlets showed the 100% survival rate (data not shown). The successful establishment of plantlet in this study was due to their micropropagation origin that is contrary to the report for Betula pendula (45). Some plantlets grow faster and exhibited higher values for all the parameters evaluated than the donor plant (see Table 3).…”
Section: Discussioncontrasting
confidence: 85%
“…The negative effect of cyclophysis due to different biological ages of rootstock and scion [20][21][22][23] appeared insubstantial, as indicated by the productivity of the plantation. Similarly, a weak effect of cyclophysis on growth and survival of vegetatively propagated silver birch has been shown in boreal conditions [24,25]. Still, grafts might have lower branchiness and branch thickness [26].…”
Section: Discussionmentioning
confidence: 92%
“…As a result, levels of genetic variation in silver birch are high within populations while the differentiation among populations is very low (Eriksson et al , Rusanen et al ). A previous study (Viherä‐Aarnio and Velling ) have shown that micropropagated silver birch plants do not differ from the seed‐born plants in growth characteristics or resistance to herbivores. Each particular genotype combination was replicated 2–6 times within the experimental area (Supplementary material Appendix 1 Table A1).…”
Section: Methodsmentioning
confidence: 94%